2010
DOI: 10.1161/strokeaha.109.566315
|View full text |Cite
|
Sign up to set email alerts
|

Internal Jugular Vein Valve Incompetence Is Highly Prevalent in Transient Global Amnesia

Abstract: Background and Purpose-Transient global amnesia (TGA) is the inability to retain new information and to recall past events during a period of minutes or hours. Its etiology is unclear, and flow disturbances in the mesial temporal lobes secondary to venous congestion have been proposed as a potential cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 25 publications
2
33
0
1
Order By: Relevance
“…The onset of transient global amnesia has been associated with activities that involve a Valsalva manoeuvre or exposure to cold water, which increase venous blood pressure. The striking symmetry of the lesions found in this patient is consistent with a haemodynamic aetiology, resulting in transiently increased venous pressure,2 3 as one might reasonably expect during a swim in the English Channel.…”
supporting
confidence: 78%
“…The onset of transient global amnesia has been associated with activities that involve a Valsalva manoeuvre or exposure to cold water, which increase venous blood pressure. The striking symmetry of the lesions found in this patient is consistent with a haemodynamic aetiology, resulting in transiently increased venous pressure,2 3 as one might reasonably expect during a swim in the English Channel.…”
supporting
confidence: 78%
“…18 Indeed, an increased prevalence of internal jugular valve insufficiency (IJVI) has been found in TGA. [10][11][12][13][14][15]28 However, recent data have shown that cerebral venous congestion does not seem to play a significant role in the pathogenesis of TGA. 29 The present study challenges also the role of intracranial vasoconstriction, which can be detected by ultrasound through direct and indirect signs: vertebral R.I. values and vertebro-basilar P.I.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that patients with TGA have IJVFR or IJVVI more frequently than control subjects, and this finding is even more prevalent in patients with TGA starting after a Valsalva maneuver. [38][39][40][41][42][43] Patients with TGA also have retrograde venous flow more commonly than patients with TIA. 39 Yet, there are some unresolved questions regarding this hypothesis.…”
Section: Pathophysiologic Mechanismsmentioning
confidence: 99%